The weight of words: writing about race in the United States and Europe - Berg, Manfred; Schor, Paul; Soto, Isabel (The American historical review, 2014)
In 1993, the historians' group in the European Association for American Studies held a meeting at the Roosevelt Studies Center in Middelburg, the Netherlands.